Analysis of the TAX1BP1 gene in head and neck cancer patients - Ruiz, Mariangela Torreglosa; Balachi, Janayna Fernanda [UNESP]; Fernandes, Raquel Aldrighi; Galbiatti, Ana Lívia Silva; Manigua, José Victor; Pavarino-Bertelli, Érika Cristina; Goloni-Bertollo, Eny Maria (FapUNIFESP (SciELO), 2010)
In Brazil, there were I4,160 new estimated cases of head and neck cancer for the year of 2008. Smoking and drinking are the main risk factors established in the etiology of this disease. Aim: to assess the T → A polymorphism in gene TAX1BP1 (leu306ile) in patients with head and neck cancer and a control population. Series and methods: a retrospective study in which we assessed the gender, age, smoking and drinking habits of 191 patients with head and neck cancer and 200 individuals without history of neoplasia. The molecular analysis was carried out after genomic DNA extraction by the PCR-RFLP method. Results: there is a predominance of males (84.82%), smokers (91.1%) and drinkers of alcohol (77.49%). Molecular assessment did not show statistically significant differences between the two groups (p = 0.32). The analysis of clinical parameters and polymorphisms showed association with oral cavity cancer (OR: 2.38; CI 95%: 1.18-4.78; p = 0.01), the other parameters were not associated with the polymorphism. Conclusion: There is evidence of association between TAX1BP1 gene polymorphism and oral cavity cancer. For the remaining parameters analyzed, the results do not suggest association with the TAX1BP1 gene polymorphism.
Keywords: Alcohol drinking; Genetics; Head and neck neoplasms; Tobacco